Heart Rate Variability and Exercise Capacity of Patients With Repaired Tetralogy of Fallot - Silvilairat S. (2014)
Heart rate variability (HRV) has been used as a reliable method to detect cardiac autonomic nervous system activity. Peak oxygen uptake (VO2 peak) has been a predictor of death for adults with repaired tetralogy of Fallot (TOF). This study investigated the correlation between HRV and exercise capacity in 30 patients with TOF after surgery for total correction. The median age of the patients was 14 years (range, 9-25 years), and the median follow-up period was 11.6 months (range, 5.3-20.2 months). Low- and high-frequency-domain HRV significantly correlated with VO2 peak (r = 0.56, P = 0.001 and r = 0.44, P = 0.02, respectively). After the 1-year follow-up evaluation, VO 2 peak and HRV analysis did not differ from those at entry to the study. However, low- and high-frequency-domain HRV still correlated significantly with VO2 peak (r = 0.43, P = 0.03 and r = 0.52, P = 0.007, respectively). Left ventricular early diastolic myocardial velocity was most closely correlated with the VO2 peak (r = 0.51, P = 0.005). Impaired cardiovascular autonomic control and left ventricular diastolic dysfunction may be responsible for exercise intolerance in patients with repaired TOF. Long-term follow-up evaluation with exercise testing and 24-h Holter monitoring are warranted. © 2011 Springer Science+Business Media, LLC.